A Survey on Crypto-Steganographic Schemes and A Use Case in Healthcare System - Mei Ling Phang; Swee Huay Heng (Journal of Engineering Technology and Applied Physics, 2019)
Information sharing has become prevalent due to the expansion of social networking in this 21st century. However, electronic devices are vulnerable to various kinds of attacks. Information might be disclosed, modified and accessed by an unauthorised third party which consequently leads to the breach of confidentiality, integrity and availability of the information. Therefore, it is of utmost importance to employ the technology of cryptography and steganography to protect information assets. Cryptography and steganography have weaknesses when they are working alone. Therefore, crypto-steganography, the combination of cryptography and steganography are introduced to overcome the weaknesses in order to provide a double layer of security and protection. This paper provides a general overview of steganography and cryptography as well as a comparison analysis of different crypto-steganographic schemes. A secure crypto-steganographic system for healthcare is then developed with the implementation and integration of the secure crypto-steganographic scheme proposed by Juneja and Sandhu. This healthcare system enables users to store and deliver message in a more secure way while achieving the main goals of both cryptography and steganography.